Gas accretion as fuel for residual star formation in Galaxy Zoo elliptical galaxies. (5th September 2019) - Davis, Timothy A; Young, Lisa M
ABSTRACT: In this letter we construct a large sample of early-type galaxies (ETGs) with measured gas-phase metallicities from the Sloan Digital Sky Survey and Galaxy Zoo in order to investigate the origin of the gas that fuels their residual star formation. We use this sample to show that star-forming elliptical galaxies have a substantially different gas-phase metallicity distribution from spiral galaxies, with ≈7.4 per cent having a very low gas-phase metallicity for their mass. These systems typically have fewer metals in the gas phase than they do in their stellar photospheres, which strongly suggests that the material fuelling their recent star formation was accreted from an external source. We use a chemical evolution model to show that the enrichment time-scale for low-metallicity gas is very short, and thus that cosmological accretion and minor mergers are likely to supply the gas in ≳ 37 per cent of star-forming ETGs, in good agreement with estimates derived from other independent techniques.